(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The article aims for a thorough textual study of the play its characters and their portrayal by the author in particular to reach to some assertion as to the author’s stand regarding socio-economic life struggles of working class women. As the title “Strife” suggests, their life is full of troubles and tribulations. How they overcome these challenges thrown at them by life and society is what makes them strong.